2018
DOI: 10.1021/acs.est.8b00341
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Basis for Ballast Water Performance Standards: “Viable/Non-Viable” or “Live/Dead”?

Abstract: The shipping industry is critical to international commerce; however, contemporary shipping practices involve uptake and discharge of ballast water, which introduces the potential for transfer of nonindigenous, invasive species among geographically distinct habitats. To counteract this hazard, regulations for ballast water management have been implemented by the International Maritime Organization (IMO) and by regulatory agencies such as the United States Coast Guard (USCG). IMO and USCG discharge standards ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…This is consistent with previous studies of UV-irradiated T. suecica [27,34,35], but also to bacteria, and yeast [42]. For samples irradiated at low UV doses, no immediate shutdown of the cellular functions occur even when the reproductive capacity is lost (i.e., live but non-viable cells) [29,38,42,43]. Non-viable cells may suffer from UV-induced DNA damages, which can be counteracted by DNA repair mechanisms [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with previous studies of UV-irradiated T. suecica [27,34,35], but also to bacteria, and yeast [42]. For samples irradiated at low UV doses, no immediate shutdown of the cellular functions occur even when the reproductive capacity is lost (i.e., live but non-viable cells) [29,38,42,43]. Non-viable cells may suffer from UV-induced DNA damages, which can be counteracted by DNA repair mechanisms [44].…”
Section: Discussionsupporting
confidence: 90%
“…However, the same samples did not meet the discharge standards of IMO and the USCG when assessing metabolism, not even after the second treatment. The different results for metabolic (living) and reproductive (viable) T. suecica cells after KBAL treatments, clearly highlights a challenge UV-based BWTS can encounter when meeting different testing regimes, which previously has been highlighted by several authors [38,39].…”
Section: Discussionmentioning
confidence: 98%
“…However, because no technology (especially new and complex technologies) is perfect, interest in requiring the release of only dead, non-viable or local/native organisms would appear reasonable. The problem remains that methods for appropriate levels of species identification, and for definitive determination of live vs. dead and/or viable vs. non-viable (including propagules and tissue fragments but excluding residual baseplates or basal shell material remaining after reactive IWC) are in dispute and often challenging and error-prone (e.g., Zaiko et al, 2016;Blatchley et al, 2018). However, where IWC systems are required to minimize discharges of the dissolved and particulate components of biocidal coatings to appropriate levels, or to treat/disinfect debris to prevent the release of possible pathogens, this secondary processing of debris will likely have a similar effect on macrofouling organisms and their propagules (Scianni and Georgiades, 2019;Georgiades et al, 2021).…”
Section: Actionable Recommendationsmentioning
confidence: 99%
“…According to Cullen (2018Cullen ( : p. 1634), there are "two fundamentally different methodologies that have been employed for enumerating potentially invasive organisms" for BWTS type approval testing: (1) stain-motility (S-M) and (2) most probable number (MPN). Research has shown evidence that the efficacy of MPN method is as efficient as S-M for verifying that BWTS meet the standards for type approval (Blatchley et al 2018; 6 Excluding ships operating in territorial waters of their flag states, ships with permanent or sealed ballast, warships and ships that discharge their ballast water to approved onshore reception facilities (Čampara et al 2019). 7 BWE is not accepted by USCG beyond 2021.…”
Section: Public Policymentioning
confidence: 99%